Relationship between salivary biomarkers and external load during a professional men's basketball game - Cabarkapa, D. V.; Cabarkapa, D.; Eserhaut, D. A.; Philipp, N. M.; Fry, A. C. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: In sports science, external load (EL) refers to the amount of physical work completed by the athletes, while internal load represents an individual physiological response to the amount of work completed during a training session. In response to a single bout of strenuous exercise, testosterone (T), as a hormone associated with anabolic processes, is likely to experience a slight increase or decrease. Alternatively, cortisol (C), as a hormone that works antagonistically to T, is likely to experience a considerably greater increase. When expressed as a testosterone-to-cortisol ratio (T/C), these two hormones serve as a viable measure of the athlete`s recovery status. Thus, the purpose of this study was to examine the relationship between EL experienced by basketball players during a game and T, C, and T/C.